Вплив способів обробки ядра насіння соняшника тиском на ступінь руйнації клітинних структур - Матюхов, Дмитро Володимирович; Кисельова, Н. М. (НТУ "ХПІ", 2009)
В статье предложена методика определения фактического содержания невскрытых клеток в масличном материале. Приведенные данные характеризуют способность к экстракции жмыха, полученного непосредственно из ядра подсолнечника в зависимости от условий прессования. Сделаны выводы о влиянии последних на результат экстракции.

Technique of the actual content determination of undestructed cells inoil-bearing material has been proposed in the paper. Datafor characterizing of extractive ability of oil-cake,obtaining directly from sunflower kernels in dependence on pressing condition were received. Conclusions about advantages and shortcomings for each case have been done.
Keywords: екстракція; розкриті клітини; нерозкриті клітини; макуха; шрот